Directionality in Signed Language Interpreting - Wang, Jihong; Napier, Jemina (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2015)
This mixed methods study investigated the effects of directionality (language direction) and age of signed language acquisition on the simultaneous interpreting performance of professional English/Auslan (Australian Sign Language) interpreters, who comprised native signers and non-native signers. Each participant interpreted presentations simultaneously from English into Auslan, and vice versa, with each task followed by a brief semi-structured interview. Unlike a similar study, results reveal no significant differences between the native signers’ English-to-Auslan simultaneous interpreting performance and their Auslan-to-English simultaneous interpreting performance, suggesting that balanced bilingual interpreters are free from the rule of directionality. Although this finding held true for the non-native signers, results indicate a need for the non-native signers to continue to enhance their signed language (L2) competence. Furthermore, although the native signers were similar to the non-native signers in overall simultaneous interpreting performance in each language direction, the native signers were significantly superior to the non-native signers in both the target text features and delivery features of English-to-Auslan simultaneous interpreting performance. These findings also suggest that the non-native signers need to further improve their signed language (L2) proficiency. Nevertheless, an analysis of the qualitative interview data reveals that the professional interpreters perceived distinct challenges that were unique to each language direction.